Koncepcja ograniczonego obowiązku podatkowego w odniesieniu do usług niematerialnych w świetle orzecznictwa i zmiany przepisów od 1 stycznia 2017 r. - Wirski, Jakub (Kwartalnik Prawa Podatkowego, 2015)
Acts on income taxes contain provisions concerning the limited tax liability concept and income derived “in the territory of Poland”. This expression is not directly defined thus it is subject to different interpretations, especially regarding taxation of intangible services. The way of interpretation of mentioned concept is exceedingly important due to the need to circumscribe the range of tax claims appertaining to Poland as a source state. In the view of foregoing, the Author presents existing interpretation lines in the jurisprudence and attempts to interpret mentioned expression. Moreover, the legal amendment of the limited tax liability concept is also described and analysed as well as its influence on an interpretation of provisions, which were in force before this amendment.